Physiological Dysregulation and Inflammation in Hospital Shift Workers - Ahmad, Dr.Taha Qasim (Academia Open, 2026)
General Background Hospital healthcare workers operate under high psychological and physical demands, executing critical patient-care tasks within complex environments. Specific Background Managing irregular schedules, continuous shift rotations, and ethical challenges puts these workers at increased risk for chronic health issues. Knowledge Gap However, the direct paths linking specific hospital stressors to autonomic and inflammatory system changes remain poorly explained due to a historical lack of objective biological indicators. Aims This study examined the relationships between night shift assignments, sleep disturbances, moral distress, and physiological markers of stress in 268 hospital professionals. Results The data show that night shift workers have significantly lower heart rate variability (RMSSD: 26.8±11.4 ms) and flattened diurnal cortisol slopes compared to day workers, alongside elevated interleukin-6 levels (3.9±2.2 pg/mL). Novelty This study provides fresh, empirical evidence of a dose-response drop in autonomic function over the first seven years of night shift work, while highlighting a unique physiological burden from moral distress. Implications These findings demonstrate an urgent need for evidence-based hospital scheduling policies, proactive sleep interventions, and systematic wellness monitoring across all clinical and support roles to protect the healthcare workforce. Keywords: Healthcare Workers, Shift Work, Heart Rate Variability, Moral Distress, Inflammation Key Findings Highlights: Night shift schedules significantly reduce resting heart rate variability and flatten natural diurnal cortisol profiles. Subjective sleep quality acts as an explicit mediator for nearly half of the relationship between night shifts and autonomic dysfunction. Elevated moral distress experiences are independently linked to significant increases in systemic pro-inflammatory cytokine levels.